Chronic toxicity of azoxystrobin to freshwater amphipods, midges, cladocerans, and mussels in water‐only exposures. (15th March 2017) - Kunz, James L.; Ingersoll, Chris G.; Smalling, Kelly L.; Elskus, Adria A.; Kuivila, Kathryn M.
Abstract: Understanding the effects of fungicides on nontarget organisms at realistic concentrations and exposure durations is vital for determining potential impacts on aquatic ecosystems. Environmental concentrations of the fungicide azoxystrobin have been reported up to 4.6 μg/L in the United States and 30 μg/L in Europe. The objective of the present study was to evaluate the chronic toxicity of azoxystrobin in water‐only exposures with an amphipod ( Hyalella azteca ; 42‐d exposure), a midge ( Chironomus dilutus ; 50‐d exposure), a cladoceran ( Ceriodaphnia dubia ; 7‐d exposure), and a unionid mussel ( Lampsilis siliquoidea ; 28‐d exposure) at environmentally relevant concentrations. The potential photo‐enhanced toxicity of azoxystrobin accumulated by C. dubia and L. siliquoidea following chronic exposures to azoxystrobin was also evaluated. The 20% effect concentrations (EC20s) based on the most sensitive endpoint were 4.2 μg/L for H. azteca reproduction, 12 μg/L for C. dubia reproduction and C. dilutus emergence, and >28 μg/L for L. siliquoidea . Hyalella azteca was more sensitive to azoxystrobin compared with the other 3 species in the chronic exposures. No photo‐enhanced toxicity was observed for either C. dubia or L. siliquoidea exposed to ultraviolet light in control water following azoxystrobin tests. The results of the present study indicate chronic effects of azoxystrobin on 3 of 4 invertebrates tested at environmentally relevant concentrations. The changes noted in biomass and reproduction have the potential to alter the rate of ecological processes driven by aquatic invertebrates. Environ Toxicol Chem 2017;36:2308–2315. Published 2017 Wiley Periodicals Inc. on behalf of SETAC. This article is a US government work and, as such, is in the public domain in the United States of America.